FORMATION OF TECHNOLOGICAL AND DESIGN COMPETENCES OF STUDENTS IN THE COURSE “MATERIALS SCIENCE OF SEWING PRODUCTION” WHILE WORKING ON DESIGN TASKS - Taranenko Tetiana (Alfred Nobel University Journal of Pedagogy and Psychology)
In the context of the modern educational process, an important aspect is the integration of theoreti- cal knowledge and practical skills that ensure the comprehensive development of future professionals. The article proposes an innovative approach to teaching, which consists in the use of design tasks as an effec- tive tool for the development of technological and design skills of students. The purpose of the article is to substantiate methodological approaches to the formation of techno- logical and design competences of students in the process of studying the educational component “Materi- als Science of Sewing Production” while performing design tasks in this course. The objectives of the article are to analyse the role and importance of design tasks in the education- al process in the study of materials science by future technology teachers; to identify the key components of technological and design competences that are formed through design tasks; to develop examples of de- sign tasks that contribute to the development of skills in material analysis, selection and design of products. Research methods are as follows: theoretical analysis, generalization, and modelling of educational situations – to develop examples of design tasks and their adaptation to the needs of the course “Materi- als Science of Sewing Production”. The importance of creative and engineering thinking of students who can self-develop, self-realise, and make decisions independently in conditions of constant change is determined. It is proved that design activity is an effective aspect that influences personal development, as it includes elements of self-expres- sion and creativity. The process of forming technological and design competence in students studying the course “Mate- rials Science of Sewing Production” is considered. The role of design tasks as a means of developing prac- tical skills to creatively approach technological problems, which stimulates the acquisition of engineering knowledge and increases the willingness to work with a variety of materials, is investigated. As a result, future specialists learn to effectively apply constructive solutions, adapting them to real production condi- tions, which is key to working in the technology industry. The main stages of training are defined, during which students apply the acquired theoretical knowl- edge of materials science in practice, selecting the design and construction for future products. In particu- lar, emphasis is placed on techniques that promote the integration of knowledge about fabric properties, processing methods and clothing manufacturing technologies. It is substantiated that the study of materials science through the prism of design tasks allows stu- dents not only to master theoretical knowledge of the characteristics of materials, their properties and ap- plication in the garment industry, but also to acquire practical skills in the process of developing designs, choosing the best materials for specific products and creating innovative models. Particular attention is paid to the analysis of the application of design tasks in practical classes, where students have the opportunity to implement their ideas through the development of real projects, including the stages of material selection, prototyping and testing of structures. Examples of tasks that contribute to the development of technical imagination, accuracy in performing tasks, and the ability to adapt to the rap- idly changing conditions of the technology industry are described. Conclusions. The positive impact of creative design tasks on the development of critical thinking, cre- ativity and technological and design competences of students in mastering technologies is outlined.